The effect of sport specialization on injury risk in NCAA athletes: Results from the SAFE Consortium - Lutsic, J. J.; Lutsic, S. E.; Ibrahim, D. S.; Augusta, M. C.; Robinson, J. D.; Tong, K. M.; Saffarian, M. R.; Nogel, S. E.; Fitton, N. J. (Clinical Journal of Sport Medicine, 2024)
Objective: Youth athletes are beginning to specialize in a single sport more often. Previous studies in sports medicine and orthopedics have shown an association between intensity of sport specialization and incidence of injuries. This study is the first of its kind to explore the effects of early sport specialization on injury risk through a multicenter framework with a concentration on NCAA athletics.